Five new species of Cleruchus from the Oriental region and report of Anaphes quinquearticulatus (Hymenoptera: Mymaridae) from India - Manickavasagam, Sagadai; Triapitsyn, Serguei V.; Palanivel, Selvaraj (Zootaxa, 2018)
An overview of the Oriental species of Cleruchus Enock (Hymenoptera: Mymaridae) is given, and its five newly described species as well as one undescribed species from Malaysia are keyed. The described new taxa are C. funiculatus Manickavasagam & Palanivel sp. n., C. indicus Manickavasagam & Palanivel sp. n. and C. orientalis Manickavasagam & Palanivel sp. n., all from India, C. blimp Triapitsyn sp. n. from Brunei, and C. pmilb Triapitsyn sp. n. from Thailand. Anaphes quinquearticulatus Huber & Triapitsyn is newly reported from India.